Management of Preoperative Meningioma Embolisation: First Case Report at Dr Soeradji Tirtonegoro Hospital Klaten - Fauzi Novia Isnaening Tyas; Huda Syahdan Al Hadad; Adika Mianoki (Magna Neurologica, 2025)
Background: Meningioma is the most common primary central nervous system tumor among benign brain tumors. Clinical manifestations vary based on the tumor's location and size, with some patients being asymptomatic and others experiencing neurological deficits. Symptomatic meningioma patients often undergo surgical management. Preoperative embolization has been shown to reduce surgical complications by minimizing intraoperative bleeding and shortening the procedure's duration. Case: A 47-years-old woman presented with progressive right limb weakness, recurrent headaches, blurred vision, and vomiting over three months, worsening in the past week. Neurological examination revealed XII nerve paresis and limb weakness. Imaging studies identified a sizeable intracranial mass with perilesional edema, leading to a diagnosis of meningioma. The patient underwent preoperative endovascular embolization followed by craniotomy and tumor excision, resulting in a favorable postoperative outcome. Her postoperative course was uneventful, with significant improvement and regular follow-up at Dr. Soeradji Tirtonegoro General Hospital. Discussions: Preoperative embolization is beneficial for selected patients with intracranial meningiomas, especially those with highly vascular tumors. This technique effectively reduces intraoperative bleeding and surgical duration, decreasing the risk of complications. Advances in embolization techniques and materials have significantly improved outcomes and expanded their applicability. Ongoing research continues to refine and optimize meningioma management, enhancing surgical success and patient prognosis. Conclusion: This case demonstrates the effectiveness of preoperative embolization in managing intracranial meningiomas. The technique reduces intraoperative complications and improves postoperative recovery, emphasizing its critical role in optimizing surgical outcomes for meningioma patients.